Effect of GaAIAs low-level laser therapy on the healing of human palate mucosa after connective tissue graft harvesting: randomized clinical trial - Dias, Stephanie Botti Fernandes [UNESP]; Fonseca, Marcus Vinícius Alves; Santos, Nídia Cristina Castro dos; Mathias, Ingrid Fernandes; Martinho, Frederico Canato; Junior, Milton Santamaria; Jardini, Maria Aparecida Neves; Santamaria, Mauro Pedrine (Springer, 2015)
Among the available techniques to treat gingival recession, connective tissue graft (CTG) presents more foreseeability and better results in the long term. However, this technique causes morbidity and discomfort in the palatine region due to graft removal at that site. The aim of this clinical trial was to evaluate the influence of low-level laser therapy (LLLT) on the healing of the donor palatine area after CTG. Thirty-two patients presenting buccal gingival recession were selected and randomly assigned to receive LLLT irradiation (test group) or LLLT sham (control group) in the palatine area after connective graft removal. A diode laser (AsGaAl, 660 nm) was applied to test the sites immediately after surgery and every other day for 7 days. The evaluated parameters were wound remaining area (WRA), scar and tissue colorimetry (TC), tissue thickness (TT), and postoperative discomfort (D). These parameters were evaluated at baseline and 7, 14, 45, 60, and 90 days after surgery. Two-way repeated measures ANOVA was used for analysis. The test group presented statistically significant smaller wounds at days 14 and 45. None of the patients presented a scar at the operated area, and colorimetry analysis revealed that there was no statistically significant difference between groups (p > 0.05). Patients reported mild to moderate discomfort, with low consumption of analgesic pills. We concluded that LLLT irradiation can accelerate wound healing on palatine mucosa after connective tissue removal for root coverage techniques (ClinicalTrial.org NCT02239042).
Keywords: Connective tissue; Gingival recession; Laser therapy; Low level; Wound healing